Controlled partial transfer hydrogenation of quinolines by cobalt-amido cooperative catalysis - Pang, Maofu; Chen, Jia-Yi; Zhang, Shengjie; Liao, Rong-Zhen; Tung, Chen-Ho; Wang, Wenguang (Nature communications, 2020)
Catalytic hydrogenation or transfer hydrogenation of quinolines was thought to be a direct strategy to access dihydroquinolines. However, the challenge is to control the chemoselectivity and regioselectivity. Here we report an efficient partial transfer hydrogenation system operated by a cobalt-amido cooperative catalyst, which converts quinolines to 1,2-dihydroquinolines by the reaction with H 3 N·BH 3 at room temperature. This methodology enables the large scale synthesis of many 1,2-dihydroquinolines with a broad range of functional groups. Mechanistic studies demonstrate that the reduction of quinoline is controlled precisely by cobalt-amido cooperation to operate dihydrogen transfer from H 3 N·BH 3 to the N=C bond of the substrates. Controlling the partial reduction of quinolines is challenging, given the competing overreduction to tetrahydroquinolines. Here, the authors report a cobalt-amido cooperative catalyst for the selective, partial transfer hydrogenation of quinolines to 1,2-dihydroquinolines with H 3 N·BH 3 as reductant.